2002
DOI: 10.1063/1.1456260
|View full text |Cite
|
Sign up to set email alerts
|

Optical control of gallium nanoparticle growth

Abstract: We report that low-intensity light can dramatically influence and regulate the nanoparticle self-assembly process: Illumination of a substrate exposed to a beam of gallium atoms results in the formation of gallium nanoparticles with a relatively narrow size distribution. Very low light intensities, below the threshold for thermally induced evaporation, exert considerable control over nanoparticle formation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 30 publications
2
50
0
Order By: Relevance
“…These methods include self-assembly during molecular beam epitaxy (MBE), 6,7 optically regulated self-assembly, 8 thermal evaporation, 9 and colloidal synthesis. 10 When exposed to atmosphere following synthesis, Ga NPs form a thin, self-terminating native oxide shell that protects the pure metallic core.…”
mentioning
confidence: 99%
“…These methods include self-assembly during molecular beam epitaxy (MBE), 6,7 optically regulated self-assembly, 8 thermal evaporation, 9 and colloidal synthesis. 10 When exposed to atmosphere following synthesis, Ga NPs form a thin, self-terminating native oxide shell that protects the pure metallic core.…”
mentioning
confidence: 99%
“…The atomic transport in adsorbing porous materials is governed by the adsoprtion/desorption events at the pore's surface, where atomic nanoaggregates are assembled as a consequence of atomic surface diffusion and nucleation [2,6,7,8]. Many experiments involving different adsorbates and substrates demonstrated that light can influence the formation of nanostructures [9,10,11,12,13,14].…”
mentioning
confidence: 99%
“…The atomic transport in adsorbing porous materials is governed by the adsoprtion/desorption events at the pore's surface, where atomic nanoaggregates are assembled as a consequence of atomic surface diffusion and nucleation [2,6,7,8]. Many experiments involving different adsorbates and substrates demonstrated that light can influence the formation of nanostructures [9,10,11,12,13,14].In particular, in porous materials loaded with alkali-metal atoms, it has been proved that atomic photo-desorption [15] plays a key role in cluster growth [6,16]. Upon visible illumination, the atomic desorption probability from atomic layers covering the pore's surface increases; consequently also the atomic diffusion coefficient, which is proportional to the desorbing rate, rises.…”
mentioning
confidence: 99%
“…The particles, typically 50 nm in diameter with a relatively narrow size distribution (±14 nm), were prepared on the tips of silica optical fibers, using the recently developed light-assisted self-assembly technique [6,7]. This process produced a nanoparticle film on the fiber's core (9 µm in diameter) comprising ∼2.…”
mentioning
confidence: 99%